The Effect of Shadow Education on Hong Kong Student Wellbeing: Evidence From PISA 2018 - Liang, Han; Wang, Zhongxing; Wu, Wensheng (Frontiers in Psychology, 2022)
The current study investigated the effect of shadow education on Hong Kong student well-being. The data were extracted from PISA 2018 of Hong Kong, and HLM analysis was conducted with student and school dimensions as independent variables and student well-being as dependent variable. The results showed that from student dimension, students attending shadow education have higher level of well-being than students who do not; from the school dimension, school competition climate has a significant impact on students’ well-being, while the variables of shadow education caused by schoolwork pressure and shadow education support have no significant impact on well-being. The interactive effect between competition climate and shadow education time negatively and significantly affected well-being. These results supported the hypothesis that appropriate participation in shadow education will enhance students’well-being in Hong Kong where educational expectation is high, and how to control the factors causing shadow education, such as competition, anxiety, pressure, probably be the key issues for further study to enhance student well-being.